2009
DOI: 10.1371/journal.pone.0007461
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Conditional Heparin-Binding EGF-Like Growth Factor Knockout Mice

Abstract: Recently, neurotrophic factors and cytokines have been shown to be associated in psychiatric disorders, such as schizophrenia, bipolar disorder, and depression. Heparin-binding epidermal growth factor-like growth factor (HB-EGF) is a member of the EGF family, serves as a neurotrophic molecular and plays a significant role in the brain. We generated mice in which HB-EGF activity is disrupted specifically in the ventral forebrain. These knockout mice showed (a) behavioral abnormalities similar to those described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 55 publications
3
34
0
Order By: Relevance
“…In conditional knock-out mice in which HB-EGF is reduced in the ventral forebrain, prefrontal cortex dopamine levels are significantly lower than in control mice (21), and these knock-out mice display behavioral abnormalities associated with psychiatric disorders. These reports suggest that HB-EGF signaling plays an important role within the dopaminergic system.…”
Section: Discussionmentioning
confidence: 98%
“…In conditional knock-out mice in which HB-EGF is reduced in the ventral forebrain, prefrontal cortex dopamine levels are significantly lower than in control mice (21), and these knock-out mice display behavioral abnormalities associated with psychiatric disorders. These reports suggest that HB-EGF signaling plays an important role within the dopaminergic system.…”
Section: Discussionmentioning
confidence: 98%
“…HB-EGF KO mice were generated using the Cre-lox-mediated conditional gene KO approach with a Six3 promoter as described previously. 36 Because they are associated with cardiac enlargement, HB-EGF KO mice died. 37 Six3 plays an important role in vertebrate visual system development.…”
Section: Animalsmentioning
confidence: 99%
“…A multiplatform profiling study identified peripheral changes that are potentially linked to central alterations in synaptic plasticity and neuronal function associated with NMDAR-NR1 hypofunction [122]. Besides the abnormal behaviors similar to those described in other schizophrenia mouse model [123], reduction of NR1 subunits was observed in mice with heparin-binding epidermal growth factor (HB-EGF) disruption. Additionally, NR1 subunits were considered as mediators of reduced Specificity Protein (Sp) transcription factors associated with negative symptoms in schizophrenia.…”
Section: Nr1 Subunits As Potential Mediators Of Convergent Molecular mentioning
confidence: 91%